Exploring the possibility of dissimilar welding of NiTi to Ti using Yb-fiber laser. Issue 4 (2nd October 2018) - Datta, Susmita; Raza, Mohammad Shahid; Kumar, Sunny; Saha, Partha
Abstract: The formation of transverse cracks in dissimilar material welding, due to difference in thermal expansion coefficient, basically restricts widespread applications of dissimilar joints. The objective of this experimental study is to evaluate the laser weldability of NiTi to Ti. An experimental work with continuous Yb-fiber laser was carried out for dissimilar material joining of 1 mm thick plates of Ti and NiTi with different heat inputs to control the cooling rate. Welding of these two materials resulted in joints with poor strength and ductility due to the formation of transverse cracks in the weld metal. Crack was always observed in Ti side of the weld metal, due to the formation of brittle Ti2 Ni phase. This was the cause behind the solidification cracking phenomena. The microstructure at the Ti side of the bead was dendritic but in the NiTi side, it was dendritic with some flower-like appearance. In between these two sides, depending upon convective material flow of the weld-bead, composition of matrix material and cooling rate, different types of microstructures were observed. The weld pool was asymmetric with a larger extent of melting taking place in the Ti side. Microhardness values gradually increased from base material to weld centerline.